Thinking Europe on Europe’s margins: Alexander Sturdza, Konstantinos Oikonomos and Russian-Greek orthodoxy in the early nineteenth century - Dialla, Ada (The Historical Review/La Revue Historique, 2020)
This article seeks to examine the construction of the notion of Europe not from a West–East perspective but from a more complex geographical and conceptual vantage point, including the north and the south in relation to the West and East and, more specifically, from the point of view of the Ggreek orthodox and Russian worlds in the postnapoleonic era. Following the political, religious and intellectual activity of two expatriates and close friends, Alexander Sturdza and Konstantinos Oikonomos, it explores how the idea of Europe was visited and how these two intellectuals and politicians negotiated and renegotiated to what extent their respective communities (Russian and Greek) were part of Europe, with religion as the central axis and the notions of the Orthodox world and Orthodox East in the arsenal of both. The first decades of the nineteenth century brought Russia and the Greeks to the forefront of the European scene. First, Russia, in the wake of its military campaigns against Napoleon’s empire (1812–1814), at the Congress of Vienna (1814–1815) found itself in a leading position in European politics and as the pacesetter in the elaboration of the idea of a united Europe. a little later, the Greek struggle for independence, the first protracted successful national struggle in Europe, raised the principle of nationalities (as national self-determination was called in the nineteenth century) for the first time as one to be reckoned with in Europe. as i argue, in the early nineteenth century the rise of Russian power provided fertile ground to challenge the idea of the secondary character of Eastern Orthodoxy in comparison to the Latin West and of the Eastern peripheral character of both Russia and Greece, and to elaborate the idea of the cultural and political equality of West and East.